2012
DOI: 10.4269/ajtmh.2012.12-0285
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Anopheles triannulatus s.l. (Diptera: Culicidae) from Northwestern and Southeastern Colombia

Abstract: Abstract. Anopheles triannulatus s.l. is a species complex, however in Colombia its taxonomic status is unclear. This study was conducted to understand the level of genetic differentiation or population structure of specimens of An. triannulatus s.l. from northwestern and southeastern Colombia. Cytochrome oxidase subunit I (COI) and internal transcribed spacer (ITS2) sequence analyses suggested high genetic differentiation between the NW and SE populations. A TCS network and Bayesian inference analysis based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 72 publications
1
15
0
9
Order By: Relevance
“…(2%), An. triannulatus lineage Northwest (NW) [41] (1.8%), An. punctimacula and Anopheles argyritarsis Robineau-Desvoidy (each at ≤ 1%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2%), An. triannulatus lineage Northwest (NW) [41] (1.8%), An. punctimacula and Anopheles argyritarsis Robineau-Desvoidy (each at ≤ 1%).…”
Section: Resultsmentioning
confidence: 99%
“…Boldfaced: collection period and name of the species with infected mosquitoes. Anopheles triannulatus specimens correspond to lineage Northwest [41]. …”
Section: Methodsmentioning
confidence: 99%
“…Previous studies of genetic variation in An. albimanus (Gutiérrez et al, 2009) and other Colombian Anopheles species have found contemporary gene flow among various MBP populations (Gutiérrez et al, 2010; Jaramillo et al, 2011; Rosero et al, 2012). Gene flow tends to homogenize the genetic background of populations, including those genes involved in phenotypic traits (Hartl and Clark, 2007), therefore, and as reported (Fusco and Minelli, 2010), the slight wing shape differences detected may be the result of phenotypic plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…albitarsis Lynch Arribálzaga, 1878, and An. triannulatus (Neiva & Pinto, 1922) (Gómez et al 2013; Gutiérrez et al 2010; Lehr et al 2005; Rona et al 2009, 2012; Rosero et al 2012; Silva-do-Nascimento et al 2011). …”
Section: Introductionmentioning
confidence: 99%